Tuberculous mycotic aneurysm of aortic arch: a case report emphasising on multidisciplinary management approach. Issue 2 (18th February 2021) - Velu, Dhivya; Ibrahim, Farrah; Hassoun, Ali
Abstract : Although tuberculosis (TB) is a well-known infection worldwide, the disease involvement in blood vessels, mainly aorta, is quite rare. The objective of this case report is to address the importance of a multidisciplinary approach aiming at successful treatment of tuberculosis, especially when presenting with mycotic aneurysm. We report a case of a 45-year-old woman with the history of sputum positive pulmonary TB, presenting with seizures and eventually found to have developed disseminated infection involving multiple organs, including the aorta. The patient was started on WHO-recommended anti-tubercular treatment but ended up requiring surgical intervention for the aneurysm. Although the main modality of treatment is the use of proper and adequate medical therapy, vascular dissemination in the form of mycotic aneurysm is difficult to be dealt singlehandedly due to their irreversible and multifactorial nature, with infection being the leading cause and their tendency to progress despite the primary infection being treated.